Sentidos de aprendizagem da docência de coordenadores e alunos do PIBID/UESPI: ressignificados da formação inicial - Pierote, Eliene Maria Viana de Figueirêdo (2016)
The objective of this thesis is to analyze the meanings attributed to learning the teaching of coordinators and undergraduate of PIBID / UESPI and the resignification of the initial formation. The study comes from the presupposition that the formation process of coordinators and undergraduates that participate of PIBID in UESPI may be influenced by a critical reflection, when it articulates itself to the theoretical and practical references of the course propitiate the reframing of the meanings of initial formation. It is intended that the understanding arising from this study, obtained based on studies (Vygotsky (2009), Gadamer (1997), initial teacher formation, as Garcia (1999), Veiga (2012), among others, on knowledge teaching, Tardif (2011), Pimenta (2002), as well as knowledge of the Initiation Program to teaching - PIBID, among other related discussions, collaborate for the renewal of thinking initial formation and institutionalizing programs in graduation. The methodology undertaken takes a qualitative study, approaching the researcher from direct contact with the situation where the studied phenomenon happens, through the importance of understanding paths, routes, movements and directions of the formative process. The investigation method is based on the principles of hermeneutics, the presuppositions of Hans-Georg Gadamer (1997), which establishes the importance of human understanding, considering its socio-historical context. The research was conducted at the Universidade Estadual do Piauí - UESPI in Teresina-PI, campi "Clovis Moura" and "Poet Torquato Neto", in Pedagogy and Mathematics courses, that participate of the Initiation Program to Teaching - PIBID and the subjects were coordinators and students of these courses. The instruments adopted for the production of data was the questionnaire, the autobiographical diary, the observation and conversation circles. Data analysis was performed through of discourse analysis technique (Bakhtin, 1997), in which the goal is to understand the other, instead of knowing an object. The findings revealed that the Mathematics and Pedagogy groups led us to the interpretation of fundamental points to our thesis, not only confirming what we raise, that the formation process of coordinators and undergraduates that participate in the PIBID in UESPI influences in the articulation of theoretical and practical reference for the learning of teaching, but increasing the chances that they themselves could reflect critically on the program and this articulation and at the same time, make inferences to the instances responsible for initial formation and transform their reality.